2021
DOI: 10.1186/s41687-021-00372-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reliability of the Dutch version of the EORTC QLQ-NMIBC24 Questionnaire Module for patients with non-muscle-invasive bladder cancer

Abstract: Background The European Organisation for Research and Treatment of Cancer (EORTC) quality of life questionnaire for non-muscle invasive bladder cancer (QLQ-NMIBC24) has been available and applied for some years now, but has yet to undergo a full comprehensive psychometric evaluation. The aim of this study was to investigate the psychometric properties of the Dutch version of the EORTC QLQ-NMIBC24 questionnaire in patients with low, intermediate and high risk NMIBC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Furthermore, the test-retest analysis indicated that the scores on this scale varied more than would be desirable in generally stable patients, and no large differences were observed for this scale in patients who experienced changes in health over time. Similar results have been observed for this scale in patients diagnosed with NMIBC [ 7 , 8 ]. However, the correlation between the items of the bloating and flatulence scale was higher for patients treated with RC compared to the total MIBC population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the test-retest analysis indicated that the scores on this scale varied more than would be desirable in generally stable patients, and no large differences were observed for this scale in patients who experienced changes in health over time. Similar results have been observed for this scale in patients diagnosed with NMIBC [ 7 , 8 ]. However, the correlation between the items of the bloating and flatulence scale was higher for patients treated with RC compared to the total MIBC population.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with other studies [ 7 , 22 , 25 ], but nevertheless resulted in the exclusion of female sexual function and the item single catheter use from the CFA. The new grouping of the items addressing sexual function is the same as proposed and confirmed for the QLQ-NMIBC24 [ 7 , 8 , 25 ], and therefore, we expect that this new grouping of the sexual items will be sustained in future studies investigating the measurement properties of the QLQ-BLM30.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Domains such as sexual functioning, self-consciousness, embarrassment, and psychological distress are of greater importance in BC patients but are not assessed thoroughly by the QLQ-C30 questionnaire [17] . Several BC-specific questionnaires have been designed to offer an instrument that closes these gaps, such as the EORTC QLQ-NIMBC24 questionnaire, which has shown excellent measurement properties with regard to validity, reliability, and responsiveness [18] , but this did not exist at the time of the original trial design.…”
Section: Discussionmentioning
confidence: 99%